Postmodern Erasing of the Shoah [Raymond Federman, Georges Perec, Anatol Ulman] - Tomczok, Marta (Poznańskie Studia Slawistyczne, 2017)
The article presents three strategies elaborated in the seventies of the last century by the postmodern prose, in order to tell us about the genocide. To name these strategies, the authoress makes use of the terms of blurring, patch, and “sous rapture”, which serve discussing Double or Nothing by Raymond Federman, W, or the Memory of the Childhood by Georges Perec, and Cigi de Montbazon by Anatol Ulman. The essential part in the discussion on the genocide is the reception of the above mentioned novels reconstructed among others on the base of works by Susan Rubin Suleiman along with her conception of the “1.5 generation”. The article also aims at a presentation of the interference between Cigi de Montbazon and European postmodernism exposed in Brian McHaleʼs idea of “worlds under erasure”. It is worth adding that the indicated presentation has not been yet considered.